PERAN TIM REAKSI CEPAT UNIT PELAYANAN KESEHATAN KANTOR KESEHATAN PELABUHAN (KKP) KELAS III BANDA ACEH PADA RESPON DINI EVAKUASI KORBAN BENCANA GEMPA BUMI (STUDI KASUS KEJADIAN GEMPA PIDIE JAYA 7 DESEMBER 2016) - Irawati .; Mudatsir .; Didik . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
Capacity Improvement of Local Quick Reaction Team (TRC) to improve technical and managerial capability for Quick Reaction Team Regional members, as Quick Reaction Team is the spearhead in the implementation of tasks in emergency disaster management. The purpose of this research is to know the Role of Quick Reaction Team of Health Service Unit of Port Health Office (KKP) of Class III of Banda Aceh on early response of emergency response of earthquake disaster victims. The research design used a qualitative approach with data collection method in Focus Group Discussion (FGD) and observation result in the field. The sample in this study is the rapid response team of health service unit KKP Class III Banda Aceh as many as 9 people (Total Population), research has Was conducted at KKP Class III of Banda Aceh on March 31st to April 21st 2017. The results showed that the role of fast response team of KKP Class III Banda Aceh health service unit in providing health service in the early response of evacuation of earthquake victims, among others, And treatment, while counseling delivered at the time of earthquake disaster one of them is the material of clean and healthy life behavior, meanwhile the information conveyed got from coordination with various sector. Understanding of the source of danger and its potential to the community should be intensified by holding it thoroughly and involving all parties, so as to increase public awareness of the earthquake hazard, and need more accurate coordination between each stakeholder in the handling of disaster victims either in one region or between Region